Удосконалення технології білково-збивного крему із застосуванням пюре з горобини і журавлини та камеді геллану - Сивній, Іванна Іванівна (My University, 2020)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.18.01 – Технологія хлібопекарських продуктів, кондитерських виробів та харчових концентратів – Національний університет харчових технологій Міністерства освіти і науки України, Київ, 2020. Дисертація присвячена удосконаленню технології білково-збивного крему із застосуванням пюре з горобини або журавлини та камеді геллану для підвищення харчової цінності, поліпшення органолептичних показників, продовження термінів зберігання. Хімічний склад плодів горобини звичайної і журавлини болотної, які ростуть на території Закарпаття, дозволив рекомендувати їх для збагачення білково-збивних кремів з метою підвищення їх харчової цінності. Розроблено технологію приготування пюре з плодів і ягід. На підставі мікробіологічних досліджень доведено, що завдяки вмісту сорбінової кислоти пюре з горобини володіє протигрибковою активністю відносно грибів роду Aspergillus і Penicillium, а завдяки вмісту бензойної кислоти пюре з журавлини володіє протидріжджовою активністю відносно дріжджів роду Candida. Встановлений позитивний вплив гелланової камеді на агрегативну стійкість білково-збивних кремів завдяки підвищенню пружних властивостей драглеподібних прошарків дисперсійного середовища та зниження витрат драглеутворювача. Доведено, що використання гелланової камеді, пюре журавлини або горобини у білково-збивних кремах сприяє зростанню міцно зв’язаної адсорбційної вологи, що дозволяє забезпечити їх стійкість до зберігання. Розроблено рецептури та удосконалено технологію білково-збивного крему «Суфле журавлинка» і «Суфле горобинове» . The dissertation on competition of a scientific degree of the candidate of technical sciences on a specialty 05.18.01 – Technology of bakery products, confectionery and food concentrates - National University of Food Technologies of the Ministry of Education and Science of Ukraine, Kyiv, 2020. The dissertation is devoted to the improvement of the technology of protein whipped cream with the use of rowan or cranberry puree and gellan gum to increase the nutritional value, improve organoleptic characteristics, extension of shelf life. Based on studies of the chemical composition of rowan berries, which grows in Transcarpathia, developed a technology for making puree of rowan berries, which involves freezing them at a temperature of minus 18… 20 ° C for 24… 36 hours, blanching the fruit with hot steam for 5 - 6 minutes, their wiping, deaeration of puree and its preservation at a temperature of 70-75 ° C. The technology of preparation of cranberry puree has been developed, which provides blanching of berries with hot steam during 5 - 6 minutes, their wiping, deaeration of puree and its preservation at a temperature of 70-75 ° С. Based on microbiological studies, it is proved that due to the content of sorbic acid rowan puree has antifungal activity against fungi of the genus Aspergillus and Penicillium, due to the content of benzoic acid cranberry puree has antifungal activity against yeasts of the genus Candida. Studies have confirmed the effectiveness of rowan and cranberry puree in creating a new range of finishing semi-finished products with high content of BAS and extended shelf life. According to the results of experimental studies, it is recommended to use gellan gum in improving the technology of protein - whipping masses in order to increase their aggregate stability by increasing the elastic properties of the gel layers of the dispersion medium and reduce the cost of gelling agent. The proposed method of preparation of whipped cream with the addition of gellan gel, cranberry or rowan puree, which includes boiling sugar molasses syrup to MCSR 90 -92%, adding puree, boiling the recipe mixture to MCSR 85%, cooling the syrup to 80 ° C, adding 50% solution of gellan gum and beating the recipe mixture with egg white. Based on the optimization by the method of multifactorial experiment, it was found that in the preparation of whipped cream the optimal amount of gellan gum is 0.55%, the amount of cranberry puree - 26.0%, with dry matter content in sugar - molasses and cranberry syrup - 86%. It is proved that the amount of gelling agent in the new sample of cream is reduced by 2.4 times compared to the cream on agar. It was found that in the preparation of protein-whipped cream with the addition of rowan puree, the amount of gellan gum is 0.5%, the amount of puree - 20%, with a dry matter content in sugar - molasses and rowan syrup - 87%. It is proved that the amount of gelling agent in the new sample of cream "Rowan
Keywords: флаваноїди; біологічно активні речовини; борошняні кондитерські вироби; білково-збивний крем; пюре з горобини; пюре з журавлини; камідь геллану; природні консерванти; сорбінова кислота; бензойна кислота; flavonoids; biologically active substances; flour confectionery; proteinwhipping cream; rowan puree; cranberry puree; gellan gum; natural preservatives; sorbic acid; benzoic acid; кафедра технології хлібопекарських і кондитерських виробів